The extent of P2Y12 inhibition by clopidogrel in diabetes mellitus patients with acute coronary syndrome is not related to glycaemic control: Roles of white blood cell count and body weight - Morel, Olivier; El Ghannudi, Soraya; Hess, Sebastien; Reydel, Antje; Crimizade, Ulun; Jesel, Laurence; Radulescu, Bogdan; Wiesel, Marie L.; Gachet, Christian; Ohlmann, Patrick (Thrombosis and Haemostasis, 2012)
It was the study objective to determine whether glycaemic control affects the extent of platelet inhibition by thienopyridines as assessed by vasodilator-stimulated phosphoprotein flow cytometry (VASP-FCT) in patients with diabetes mellitus (DM) undergoing percutaneous coronary intervention (PCI) during acute coronary syndrome (ACS). Although the proportion of high on-treatment residual platelet reactivity is higher in DM, the contributions of glycaemic control and other factors associated with DM, such as excess body weight and inflammation, to this impaired platelet inhibition by thienopyridines have not yet been fully characterised. In this study, the extent of P2Y12 ADP receptor pathway inhibition was evaluated by the VASP-FCT. Platelet activation was expressed as the platelet reactivity index (PRI). Low response to clopidogrel (LR) was defined as a PRI of >61%. Four hundred forty-five consecutive ACS patients (DM = 160, NDM = 285) were enrolled. The proportion of LR was higher in DM patients (50 vs. 37.5%). In DM, PRI was not correlated with glycosylated haemoglobin (HbA1c) or glycaemia. In a univariate analysis, LR was associated with age, male sex, overweight, and white blood cell count (WBC). In a multivariate analysis, WBC >10,000 and body weight >80 kg were the sole independent predictors of LR to clopidogrel (hazard ratio (HR) 3.02 [1.36–6.68], p=0.006 and HR 2.47 [1.14–5.35], p = 0.021, respectively). Conversely, in non-DM patients, ST-elevation myocardial infarction was the sole independent predictor of LR. In conclusion, in ACS DM patients undergoing PCI, the extent of P2Y12 inhibition by clopidogrel is not related to glycaemic control but is related to body weight and inflammatory status as assessed by the WBC.
Keywords: Thienopyridines; resistance; platelet; stent thrombosis; acute coronary syndrome; inflammation; obesity; leukocyte